Combination of Fat-Free Muscle Index and Total Spontaneous Portosystemic Shunt Area Identifies High-Risk Cirrhosis Patients - Faron, Anton; Abu-Omar, Jasmin; Chang, Johannes; Böhling, Nina; Sprinkart, Alois Martin; Attenberger, Ulrike; Rockstroh, Jürgen K.; Luu, Andreas Minh; Jansen, Christian; Strassburg, Christian P.; Trebicka, Jonel; Luetkens, Julian; et al. (Frontiers in Medicine, 2022)
BACKGROUND: Sarcopenia and spontaneous portosystemic shunts (SPSS) are common complications of liver cirrhosis, and both are associated with higher rates of hepatic encephalopathy (HE) development in these patients. This study aimed to evaluate the simultaneous impact of skeletal muscle mass and spontaneous portosystemic shunting, measured from routine diagnostic computed tomography (CT), on outcome in patients with liver cirrhosis. METHODS: Retrospective analysis of cirrhotic patients. Skeletal muscle mass (including fat-free muscle index (FFMI) as surrogate for sarcopenia) and total cross-sectional spontaneous portosystemic shunt area (TSA) were quantified from CT scans. Primary endpoint was development of HE, secondary endpoint was 1-year mortality. RESULTS: 156 patients with liver cirrhosis were included. Patients with low (L-) FFMI and large (L-)TSA showed higher rates of HE development. In multivariable analysis, L-FFMI and L-TSA were independent predictors of HE development (L-FFMI HR=2.69, CI 1.22-5.93; L-TSA HR=2.50 CI=1.24-4.72) and 1-year mortality (L-FFMI, HR=7.68, CI 1.75-33.74; L-TSA, HR=3.05, CI 1.32-7.04). Simultaneous presence of L-FFMI and L-TSA exponentially increased the risk of HE development (HR 12.79, CI 2.93-55.86) and 1-year mortality (HR 13.66, CI 1.75-106.50). An easy sequential algorithm including FFMI and TSA identified patients with good, intermediate and poor prognosis. CONCLUSION: This study indicates a synergy between low skeletal muscle mass and large TSA to predict exponentially increased risk of HE development and mortality in liver cirrhosis. Simultaneous screening for sarcopenia and TSA from routine diagnostic CT may help to improve identification of high-risk patients using an easy-to-apply algorithm. ClinicalTrials.gov Identifier: NCT03584204.